Internationalization of the nuclear fuel cycle : goals, strategies, and challenges (National Academies Press, 2009)
"The so-called nuclear renaissance has increased worldwide interest in nuclear power. This potential growth also has increased, in some quarters, concern that nonproliferation considerations are not being given sufficient attention. In particular, since introduction of many new power reactors will lead to requiring increased uranium enrichment services to provide the reactor fuel, the proliferation risk of adding enrichment facilities in countries that do not have them now led to proposals to provide the needed fuel without requiring indigenous enrichment facilities. Similar concerns exist for reprocessing facilities. Internationalization of the Nuclear Fuel Cycle summarizes key issues and analyses of the topic, offers some criteria for evaluating options, and makes findings and recommendations to help the United States, the Russian Federation, and the international community reduce proliferation and other risks, as nuclear power is used more widely. This book is intended for all those who are concerned about the need for assuring fuel for new reactors and at the same time limiting the spread of nuclear weapons. This audience includes the United States and Russia, other nations that currently supply nuclear material and technology, many other countries contemplating starting or growing nuclear power programs, and the international organizations that support the safe, secure functioning of the international nuclear fuel cycle, most prominently the International Atomic Energy Agency."--Publisher's description